Digital Transformation Towards New Frontiers and Business Opportunities - Petrillo, Antonella; De Felice, Fabio; Violeta Achim, Monica; Mirza, Nawazish (IntechOpen, 2022)
In the business world, digital transformation involves finding and developing new strategies and modernizing the information technology of private and public companies. This book presents practices, challenges, and opportunities related to digital transformation. It includes fourteen chapters that address digital transformation in a variety of industries, including finance, construction, education, marketing, and more.